Preliminary investigation of hematozoan in laughing Dove (Spilopelia senegalensis) in Suleimani Province - Kwestan Najm Ali (Basrah Journal of Veterinary Research)
Spilopelia senegalensis, a species of laughing dove native to Iraq, has successfully adapted to the Kurdistan Region. The world's sub-Saharan Africa, Arabia, Iran, Iraq, Afghanistan, Pakistan, India and some other Middle East countries were among the regions it settled. The laughing dove first appeared in the middle and southern regions of Iraq in 2005. In the current study, 100 laughing doves (Spilopelia senegalensis), of various ages and sexes, were examined microscopically using blood smears stained with Giemsa. Fecal samples were aseptically taken from the intestines after the birds had been slaughtered and fully bled. Both centrifugal sedimentation and flotation techniques were used to analyze the fecal samples. The results of the investigation showed that 43 out of 100 doves (43% of them) had a plasmodium species infection. We documented that the most infective parasite infection in doves and this will be the first report in Sulaimani Province, Kurdistan Region, Iraq.